In utero perfluorooctane sulfonate exposure causes low body weights of fetal rats: A mechanism study. (March 2016) - Li, Xiaoheng; Ye, Leping; Ge, Yufei; Yuan, Kaiming; Zhang, Yufei; Liang, Yong; Wei, Jia; Zhao, Connie; Lian, Qing-Quan; Zhu, Xueqiong; Ge, Ren-Shan
Abstract: Objectives: The objective of the present study is to investigate the mechanism of perfluorooctane sulfonate-induced low body weight of fetus by analysis of glucocorticoid metabolizing enzyme 11β-hydroxysteroid dehydrogenase 2 and gene expression profiling of the placenta after in utero PFOS exposure. Study design: Pregnant Sprague–Dawley dams were gavaged with 0, 5, and 20 mg/kg body weight PFOS daily from gestational day 12–18. On gestational day 18, pregnant dams were euthanized, placentas, and fetuses were collected. Main outcome measures: Body weights of fetuses and placentas were measured, the corticosterone levels in fetal serum, and 11β-hydroxysteroid dehydrogenase 2 as well as the placental gene profiling were analyzed. Results: 20 mg/kg PFOS significantly reduced fetal body weight and placental weight. Both 5 and 20 mg/kg PFOS increased fetal serum corticosterone levels. PFOS potently inhibited placental 11β-hydroxysteroid dehydrogenase 2 activity. Of 21, 910 genes, 45 genes were significantly downregulated ≥2 fold by 20 mg/kg PFOS, including extracellular matrix ( Slpi and Pi16 ), growth factors and hormones ( Trh and Pdf ), ion transporters ( Aqp1, S100a4, and Abp1 ), signal transducers ( Kap and Ampd3 ), and structural constituents ( A2m and Des ). Conclusions: PFOS exposure may alter placental development and function, causing intrauterine growth restriction via inhibiting placental 11β-hydroxysteroid dehydrogenase 2. Highlights: PFOS inhibits rat placental 11β-hydroxysteroid dehydrogenase 2. PFOS increases corticosterone level in fetal serum after in utero exposure. PFOS alters placental gene expressions related to nutrition transportation.